1987
DOI: 10.1159/000111608
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Appearance of Glycoconjugate with Terminal N-Acetylgalactosamine on the Surface of Selected Neurons in Mouse Brain

Abstract: Selected neurons in the cortex and other regions of the brain of adult mice stain with Vicia villosa agglutinin (WA) conjugated to horseradish peroxidase (HRP). This staining demonstrates glycoconjugate with terminal N-acetylgalactosamine (GalNAc) in periodic foci on the neuronal surface. However, brains from mice at 1 week of age lacked neurons with surface reactivity for VVA-HRP but showed neurons with faint cytoplasmic staining. Two weeks postnatally, infrequent cortical neurons located mostly in layer IV d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
7
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 10 publications
4
7
0
Order By: Relevance
“…The regional distribution and the time course of the appearance of PNs during postnatal development of the wild-type mice correspond with the data obtained in ICR mice by lectin staining (Nakagawa et al, 1987;Murakami et al, 1997) and in C3B6 mice by the detection of "glucuronic acid-and-sulphate-containing glycoproteins" (Yamamoto et al, 1988). The patterns also resembled those known from cytochemical studies in the rat (Watanabe et al, 1989;Fujita and Kudo, 1992;Seeger et al, 1994;Köppe et al, 1997a).…”
Section: Developmental Profiles Of Perineuronal Nets In Wild-type Anisupporting
confidence: 84%
See 1 more Smart Citation
“…The regional distribution and the time course of the appearance of PNs during postnatal development of the wild-type mice correspond with the data obtained in ICR mice by lectin staining (Nakagawa et al, 1987;Murakami et al, 1997) and in C3B6 mice by the detection of "glucuronic acid-and-sulphate-containing glycoproteins" (Yamamoto et al, 1988). The patterns also resembled those known from cytochemical studies in the rat (Watanabe et al, 1989;Fujita and Kudo, 1992;Seeger et al, 1994;Köppe et al, 1997a).…”
Section: Developmental Profiles Of Perineuronal Nets In Wild-type Anisupporting
confidence: 84%
“…In mice, the first PNs in the cerebral cortex appear after the second postnatal week as shown by specific lectin staining. PNs associated with neurons in subcortical nuclei develop earlier (Nakagawa et al, 1987;Murakami et al, 1997).…”
mentioning
confidence: 99%
“…In a number of studies dealing with the structure and chemical nature of PNs it was shown that they represent accumulations of extracellular matrix composed of large aggregating chondroitin-sulphate proteoglycans (CSPGs) associated with hyaluronan (DeYoe et al 1990;Brauer et al 1993;Brückner et al 1993;Bertolotto et al 1996). These components have been cytochemically detected by the use of specific antibodies, lectins and basic dyes (Nakagawa et al 1987;Girard et al 1992;Härtig et al 1992;Brückner et al 1993Brückner et al , 1996aSchweizer at al. 1993;Celio and Blümcke 1994;Yasuhara et al 1994;Bertolotto et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the situation in mammals, SBA labels the surface of only a (sub)population of olfactory neurones in eels (Franceschini and Ciani, 1991) and frogs (Hofmann and Meyer, 1991;Key and Giorgi, 1986), but does not label other cells in the central nervous system of these animals. In mice it has been shown that viciu uillosa agglutinin, which labels essentially the same cells as SBA (Kosaka and Heizmann, 19891, fails to produce the typical labelling pattern in 1 week old animals (Nakagawa et al, 1987). Adult-like labelling was observed by the age of 3 weeks.…”
Section: Discussionmentioning
confidence: 99%